Can restorative justice reduce battering? Some preliminary considerations - Presser, Lois (Social justice, 2000)
Part of a special section on race, class, and state crime. The writers analyze the potential of restorative justice programs to lower the incidence of domestic violence. They explore current interventions that depend, respectively, on the power of law and the power of dialogue to stem domestic violence. In addition, they outline the restorative justice philosophy and discuss the promises and the problems of restorative justice interventions for domestic violence. Furthermore, they consider the lessons of the shelter movement, which has taken both legal and extralegal action, for developing restorative justice responses to battering.